CENTRALIZING MAPPINGS OF PRIME AND SEMIPRIME*-RINGS - Majeed, A.; Altay, A. (Iraqi Journal of Science, 2024)
In this paper we prove the following result. Let R be a non-commutative prime*-ring of characteristic different from 2, then R is normal *-ring if and only if thereexists a nonzero Jordan*-derivation d: R→R be which satisfies [d(x), x] ∈ Z(R) forall x ∈ R, and [d(h),s] ∈ Z(R) or [d(s), h] ∈ Z(R) for all h ∈ H(R), s ∈ S(R).